Gambaran Pengetahuan dan Sikap Kesiapsiagan Bencana Banjir pada Siswa di SMP N 6 Surakarta - Puji Lestari; Ika Silvitasari (Jurnal Medika Nusantara, 2026)
Flooding frequently occurs in Indonesia, including in the city of Surakarta, and SMP Negeri 6 Surakarta is one of the schools affected. These events disrupt the learning process, damage facilities, and cause losses, demonstrating that schools are also vulnerable to disasters. Knowledge plays an important role in shaping students’ preparedness attitudes when facing emergency situations. Therefore, it is necessary to assess the level of students’ knowledge and preparedness attitudes related to flood disasters. This study aims to describe the knowledge and preparedness attitudes of students at SMP Negeri 6 Surakarta toward flood disasters. This research employed a quantitative descriptive method with a Simple Random Sampling technique involving 88 respondents. The research instruments consisted of questionnaires on knowledge and preparedness attitudes using a Likert scale, which had been tested for validity and reliability. The results showed that the majority of students’ knowledge levels were in the good category (95.5%), followed by the moderate category (3.4%) and the poor category (1.1%). Meanwhile, most students’ preparedness attitudes were also classified as good (90.9%), moderate (8.0%), and poor (1.1%). Kata kunci: Banjir, Kesiapsiagan, Pengetahuan, Sikap, Siswa